"I'M DYING TO BE A STAR": AN EXPLORATORY RESEARCH ON THE DEMAND IN SINGING COURSES IN PUBLIC SCHOOLS OF VOCATIONAL EDUCATION - Paulo Constantino; Márcia Regina de Oliveira Polentine (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
Analyzes the significant increase in demand for the vocational education in Singing, in a São Paulo State public institution in recent years. Based on documentary research, combined with the analysis obtained with a focus group of new students in 2014, are considered some explanations for this demand. Expectations of fame and stardom - strongly nourished by the candidates - was initially investigated as the hypothesis.